THE ROLE OF UMKM IN DRIVING THE LOCAL ECONOMY: A LITERATURE ANALYSIS - Hety Devita; Muhamad Eko Wahyu Umaryadi; Wahab Wahab (JOURNAL OF COMMUNITY DEDICATION, 2023)
MSMEs (Micro, Small and Medium Enterprises) have an important position in running the wheels of regional economic growth by creating jobs, reducing unemployment, and strengthening economic inclusion in various regions. This research discusses the vital role of MSMEs in empowering the local economy through job creation, increasing competitiveness through product innovation, and contributing to local revenue. In addition, MSMEs also drive the growth of supporting industries such as logistics, marketing, and wholesale trade, ultimately creating a more open and sustainable business ecosystem. However, to make the most of the role of MSMEs, several strategic measures are needed, including strengthening access to capital and financing through the People's Business Credit (KUR) programme and financial technology, improving the quality of human resources through entrepreneurship and management training, and improving physical and digital infrastructure. In addition, the government needs to develop policies and regulations that support the growth of MSMEs by simplifying the licensing process, providing tax incentives, and ensuring strong legal protection for MSME players. This study concludes that with the right policy support and coordinated strategic measures, MSMEs have great potential to become a resilient and sustainable engine of the local economy, and contribute significantly to open national economic growth.